(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze treatment costs according to patient characteristics, drug utilization characteristics, and factors related to the treatment costs of pediatric patients with invasive Candida infections at Children’s Hospital 2. Subjects and methods: A descriptive cross-sectional, retrospective study on 273 medical records of pediatric patients with invasive Candida infections during the period 2022–2023. Results: The median total treatment cost for pediatric patients with invasive Candida infections was 95,734,470 VND (range: 45,743,101 – 160,596,329 VND). The majority of treatment costs were covered by health insurance, accounting for 95.73%. Medication costs represented 34.59% of the total treatment cost. Caspofungin was the antifungal agent with the highest median cost at 51,004,800 VND (range: 31,911,040 – 80,085,950 VND). Candida parapsilosis was the most frequently isolated species and also contributed the highest proportion of treatment costs (>30% of the total treatment cost). Linear regression analysis suggested that factors such as changes in antifungal therapy and length of hospital stay were associated with increased treatment costs. Conclusion: The study results provided preliminary data on the treatment costs of invasive Candida infections in pediatric patients, highlighting the need for appropriate treatment strategies and early interventions to reduce the financial burden on the public healthcare system in Vietnam.